Pengaruh Online Advertising, Brand Image Dan Price Terhadap Keputusan Pembelian Pada Produk Skincare The Originote (Studi Kasus Pada Mahasiswa Ekonomi Bisnis UNISMA) - Anggarani, Huwaina Tryas; Wahono, Budi; Wahyuningtyas, Nanik (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to analyze the influence of online advertising, brand image and price on purchasing decisions. The population in this study were Business Economics students at the Islamic University of Malang. This research uses a quantitative type of research, with a sampling method using a purposive sampling technique which is used based on certain criteria using a questionnaire distributed to 97 respondents. This research method uses multiple linear regression analysis with the SPSS 25 analysis tool. With the results of the multiple linear regression test, online advertising and brand image have a positive effect on purchasing decisions, while price has a negative effect on purchasing decisions. Based on the results of the hypothesis test, it is known that simultaneously online advertising, brand image and price have a significant influence on purchasing decisions, partially online advertising, brand image and price have a significant influence on purchasing decisions. Keywords: Online Advertising, Brand Image, Price, Purchasing Decisions